Inovasi Pangan Berbahan Dasar Blondo pada KUB HRG BERJAYA Kelurahan Sidomulyo Barat - Sujarwati, Sujarwati; Isda, Mayta Novaliza; Titrawani, Titrawani; Lestari, Wahyu; Susanto, Eki (Journal of Community Engagement Research for Sustainability, 2024)
The formation of a joint business group is based on the fact that there are many community members who want to start a business but do not have the capital and courage to do business. Community group empowerment activities have proven to be able to make the product better known, increase the number of orders and the income of group members. Virgin Coconut Oil is one example of coconut milk fermenting business for 24 hours to form VCO and dregs. This dregs is called blondo which can be converted into various kinds of processed products so as to reduce environmental pollution. The method used in its application is modeling, training and mentoring. Based on the results of these activities, community service activities have succeeded in improving the skills of KUB HRG BERJAYA members in producing innovative blondo-based foods, namely blondo sauce and blondo abon. Service activities have also succeeded in improving the skills of KUB HRG BERJAYA members in online marketing. Production and marketing assistance activities have also marketed many products. The result is an increase in the income of KUB and KUB members.